CLASS ACTION IN LITHUANIA – PRACTICAL IMPLEMENTATION ISSUES - Daujotas, Rimantas (Teisė, 2017)
Article identifies the basic practical problems of implementing the class action, determines what challenges await the parties and the courts after introduction of this new and yet well-untested institute in Lithuania. In addition, article provides suggestions for regulatory improvement of this institute, given the problems that arise in other jurisdictions, in such a way ensuring that the class action could become not a declarative, but real and genuine tool to a large group of victims to defend their rights in court, and for the business to avoid becoming victim of abused application of this tool.